Treponema pallidum pallidum Genotypes and Macrolide Resistance Status in Syphilitic Lesions among Patients at 2 Sexually Transmitted Infection Clinics in Lima, Peru. Issue 7 (July 2016) - Flores, Juan Antonio; Vargas, Silver Keith; Leon, Segundo Ramos; Perez, Danny Giancarlo; Ramos, Lourdes Beatriz; Chow, Jeremy; Konda, Kelika Anne; Calvo, Gino Mauricio; Salvatierra, Hector J.; Klaussner, Jeffrey D.; Caceres, Carlos Fernando
Abstract : Abstract: We report the circulating genotypes and the frequency of macrolide-resistance patterns among Treponema pallidum pallidum DNA isolated from syphilitic lesions from patients who attended 2 sexual health clinics in Lima, Peru. We implemented and used a molecular typing scheme to describe local T. pallidum pallidum strains. Among 14 specimens, subtype 14d/f was the most prevalent strain in 7 fully typed T. pallidum DNA specimens obtained from men who have sex with men and transgender women presenting with chancre-like lesions. No macrolide-resistance mutations were found in T. pallidum DNA from 10 lesions. Abstract : By using the Treponema pallidum enhanced typing procedure, we found that subtype 14d/f was the most prevalent strain among fully typed T. pallidum DNA specimens and no macrolide-resistant strains were found.